Polypharmacy and potential drug-drug interactions among medications prescribed to chronic kidney disease patients - Chaudhary, Shrijana Kumari; Manadhar, Naresh; Adhikari, Laxman (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Chronic kidney disease is a major systemic condition. Presence of comorbid conditions with the deteriorating renal function, lead them to use multiple drugs. Polypharmacy is common among chronic kidney disease. The possibility of drug interaction rises when a patients concurrently receive more than one drug and the chances increase with the number of drugs taken, which may be associated with increased morbidity, mortality, length of hospital stay and health-care cost. The aim of this study was to assess the polypharmacy and pattern of drug- drug interactions in chronic kidney disease patients attending OPD and ward of nephrology unit in Kathmandu Medical College teaching hospital. Material and Methods: This was a prospective cross sectional study conducted among 143 chronic kidney disease diagnosed patients in Kathmandu Medical College Teaching Hospital. The Lexi-comp database was used to evaluate patient’s medications for potential drug-drug interactions. Results: Chronic kidney disease was predominant among male (65.7%) than the female (34.3%). The most common age group was 41-60yrs followed by 61-80 yrs. The mean age of the patients was 54.38 ± 16.43 years. Chronic kidney disease was associated with multiple co-morbid conditions. The most common comorbid conditions were hypertension 52 (36. 4%) and hypertension and diabetes both in 42 (29.4%). A total of 143 prescriptions were included in this study. Average number of drugs per prescription was 6.1. Almost 5-8 medicines per prescription were observed among 95(65.73%) patients. A total of 837 medicines were prescribed. A total number of 206 potential drug-drug interactions were observed among 143 patients. Depending upon the risk rating categorize, the most common were, risk rating C 178( 86.4%) and the most frequent drug interaction was between amlodipine and calcium carbonate 65 (45.45%) . Conclusion: The prevalence of potential drug-drug interaction is high among chronic kidney disease patients. About 63% of interactions have moderate severity. The safest approach to avoid potentials drug-drug interaction is the implementation of appropriate guidelines, detailed and rationalize knowledge of drugs and to utilize available drug-drug interaction software to avoid harmful drug-drug interaction among chronic kidney disease patients.